Načrt finančnega prestrukturiranja - Plavšak, Nina (Podjetje in delo, 2014)
Restructuring plan shall comprise a description of all intended restructuring measures and estimate of their effects on ensuring debtor's liquidity and solvency.
Keywords: dolgovi; insolventnost; nelikvidnost; podjetja; prestrukturiranje